2022
DOI: 10.15294/jpfi.v18i1.30534
|View full text |Cite
|
Sign up to set email alerts
|

Science Process Skills and Critical Thinking Ability Assessed from Students' Gender

Abstract: Science process skills and critical thinking are skills that are very important and must be possessed by students in the 21st century. The purpose of this study is to determine the scientific process and critical thinking skills in terms of gender and see whether there is a relationship between science process skills and critical thinking skills. student. This is because the researcher wants to see a comparison of the abilities of male and female students. This research is a type of quantitative research with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…STEM approaches can also build science process skills (Kizilay et al 2018;U. Sari et al 2020;Darmaji et al 2022Darmaji et al , 2021Vooren et al 2022) .…”
Section: The Relationship Between Critical Thinking Skills and Scienc...mentioning
confidence: 99%
See 1 more Smart Citation
“…STEM approaches can also build science process skills (Kizilay et al 2018;U. Sari et al 2020;Darmaji et al 2022Darmaji et al , 2021Vooren et al 2022) .…”
Section: The Relationship Between Critical Thinking Skills and Scienc...mentioning
confidence: 99%
“…Research that also states the relationship between critical thinking skills and science process skills is Darmaji et al (2022Darmaji et al ( , 2021 , Irwanto et al (2019) , Kurniawan et al 2020) , Rohani (2013) , and Tanti et al (2020 . These studies state that critical thinking skills and science process skills have a relationship.…”
Section: The Relationship Between Critical Thinking Skills and Scienc...mentioning
confidence: 99%
“…Unresolved problems regarding the optical kit include that most students still need help with using the optical kit [17]. Schools already have optical kits, but these optical kits are rarely used because their use is rather complicated [20]. The light refraction experiment activities carried out by students showed that most students still needed to be more skilled in using kit tools.…”
Section: Introductionmentioning
confidence: 99%
“…One of the expected skills is science process skills (Elvanisi et al, 2018). Science process skills are one of the most used thinking skills (Darmaji et al, 2022;Gültekin & Altun, 2022). Any individual who cannot use science process skills will have difficulties in everyday life, because these skills are not only used during education, but also used in everyday life (Waruwu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%